The politics of corruption : the election of 1824 and the making of presidents in Jacksonian America - Callahan, David P., 1962- (University of Virginia Press, 2022)
"This book looks at how the five men who ran for president in 1824-Treasury Secretary William Crawford, Secretary of State John Quincy Adams, Secretary of War John C. Calhoun, Speaker of the House Henry Clay, and General Andrew Jackson-mixed traditional, elitist tactics with new, democratic methods to achieve their goals. Because it retained elements of Early Republic presidential elections, but it also pioneered new Jacksonian Era aspects, the presidential election of 1824 served as a transitional contest between the two eras"--